Evaluation of a Neonatal Resuscitation Training Programme for Healthcare Professionals in Zanzibar, Tanzania: A Pre-post Intervention Study - Ding, Xiang; Wang, Li; Msellem, Mwinyi I.; Hu, Yaojia; Qiu, Jun; Liu, Shiying; Zhang, Mi; Zhu, Lihui; Latour, Jos M. (Frontiers in Pediatrics, 2021)
Background: Neonatal mortality rates remain high in Sub-Sahara African countries. Improving healthcare professionals’ newborn resuscitation skills is important in addressing this challenge. The aim of this study was to evaluate a neonatal resuscitation training program, delivered over a two-year period, for healthcare professionals in Zanzibar, Tanzania. Methods: A pre- and post-intervention study was designed. We delivered the neonatal resuscitation training over a 2-day period in 2017 and a 2-day refresher training in 2018. Knowledge was evaluated by a self-designed survey (11 items with a total score of 22) before and after the two training periods and skills were evaluated by a skills-checklist (six domains with 25 items with a total score of 50) completed by observations of trainers. Statistical analysis included differences of knowledge and skills scores before and after the training sessions and between the two periods. Results: A total of 23 healthcare professionals participated and completed both neonatal resuscitation training sessions. Knowledge mean scores before and after the training in 2017 increased from 9.60 to 13.60 (95%CI: -5.900;-2.099, p<0.001) and in 2018 the scores increased from 10.80 to 15.44 (95%CI: -6.062;-3.217, p<0.001). Knowledge mean scores post-training over time were 13.60 in 2017 and 15.44 in 2018 (95%CI: -3.489;0.190, p=0.030). The resuscitation skills performance between the two time periods increased from mean 32.26 (SD=2.35) to mean 42.43 (SD=1.73), (95%CI: -11.402,-8.945, p<0.001). Conclusion: The neonatal resuscitation training program increased the theoretical knowledge and resuscitation skills before and after the two training sessions and over time after a 9-month period. Continuous neonatal resuscitation training based on the local needs in resource limited countries are essential for healthcare professionals to provide confidence in initiating resuscitation and to improve newborn outcomes.